1989
DOI: 10.1902/jop.1989.60.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Different Cross‐Linked Types of Collagen Implanted in Rat Palatal Gingiva

Abstract: Collagen membrane preparations were manufactured with the aim of enhancing wound healing following periodontal surgery. After crosslinking by various processing methods (with ultraviolet and hexamethylenediisocyanate) and to various extents, two types of collagen (atelocollagen and tendon collagen) were implanted into a dissection site within palatal gingival tissue. The time course of healing responses was investigated histologically. Collagen implantation was found to accelerate fibrous connective tissue att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 21 publications
0
62
0
Order By: Relevance
“…This means that the number of collagen crosslinks is proportional to both the stiffness of the membrane and the degradation time. 6,7 The most frequently used crosslinking method is to tan the collagen with glutaraldehyde (GA), which, although an effective cross-linking agent, has been shown in vitro 8 and in vivo 9 to increase the cytotoxicity of collagen membranes. GA is released during collagen degradation, and a constant release of remnant (non reacted) GA has been shown to inhibit cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the number of collagen crosslinks is proportional to both the stiffness of the membrane and the degradation time. 6,7 The most frequently used crosslinking method is to tan the collagen with glutaraldehyde (GA), which, although an effective cross-linking agent, has been shown in vitro 8 and in vivo 9 to increase the cytotoxicity of collagen membranes. GA is released during collagen degradation, and a constant release of remnant (non reacted) GA has been shown to inhibit cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical application of SFM Silk membrane plus 3% 4-hexylresorcinol (3% 4-HR + SM), collagen membrane (CM). In an in vitro study of rat palatal gingiva, migration and downgrowth of the epithelium occurred after 2 weeks of GBR Minabe et al 1989). Migration of bone and periodontal ligament cells to a bone defect reaches peak activity 2 to 7 days after initiating GBR and then decreases to almost normal levels 21 days later (Iglhaut et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effectiveness of the collagen membrane was debated in regeneration literature because of its relatively fast resorption rate even after cross-linking. However, recently reported evidence suggested that since the epithelial proliferation occurs within the first 14 days of periodontal wound healing, it is postulated that the period of time in which a collagen membrane remains intact is sufficient to inhibit epithelial migration (19,21).…”
Section: Bioabsorbable Barrier Membranesmentioning
confidence: 99%